Serine protease inhibitors of the whirling disease parasite Myxobolus cerebralis (Cnidaria, Myxozoa): Expression profiling and functional predictions. - Edit Eszterbauer; Dóra Szegő; Krisztina Ursu; Dóra Sipos; Ákos Gellért (PLoS ONE)
Here, we studied the expression pattern and putative function of four, previously identified serine protease inhibitors (serpins) of Myxobolus cerebralis, a pathogenic myxozoan species (Cnidaria: Myxozoa) causing whirling disease of salmonid fishes. The relative expression profiles of serpins were determined at different developmental stages both in fish and in annelid hosts using serpin-specific qPCR assays. The expression of serpin Mc-S1 was similar throughout the life cycle, whereas a significant decrease was detected in the relative expression of Mc-S3 and Mc-S5 during the development in fish, and then in the sporogonic stage in the worm host. A decreasing tendency could also be observed in the expression of Mc-S4 in fish, which was, however, upregulated in the worm host. For the first time, we predicted the function of M. cerebralis serpins by the use of several bioinformatics-based applications. Mc-S1 is putatively a chymotrypsin-like inhibitor that locates extracellularly and is capable of heparin binding. The other three serpins are caspase-like inhibitors, and they are probably involved in protease and cell degradation processes during the early stage of fish invasion.